Visual Analysis of Current Research Status of Sichuan Opera and Application in Leather Products - Wantong ZHAO; Xiaobing ZHANG; Luming YANG (Pige Kexue Yu Gongcheng)
Sichuan opera, as one of the traditional Chinese local operas, has a colorful art form and can be called an excellent representative of Ba Shu culture. Using CiteSpace software, we visualized and analyzed the current situation about the research and development of Sichuan opera and fully understood its research hotspots and trends, which lays a theoretical foundation for the application of Sichuan opera elements in modern product design. We applied the Sichuan opera face elements in bags, keychains and other leather products to carry out innovative design practice, to realize the harmonious intermingling of traditional culture and modern design, to improve the uniqueness and recognition of the products, and to increase their cultural connotation and market competitiveness. This design practice further broadened the modernization application of Sichuan opera elements, and opened up a new road for the inheritance and innovation of traditional culture.